2014
DOI: 10.1159/000367854
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an Association between a Functional Polymorphism in the Neuropeptide Y Gene Promoter and the Presence of Coronary Artery Disease in an Iranian Population

Abstract: Background/Aims: Several genetic factors have been identified that may contribute to the risk of coronary artery disease (CAD). Variants of the neuropeptide Y (NPY) gene, whose products play an important role in regulating several physiological functions, have been associated with the risk of CAD in some populations. The purpose of this study was to investigate the relationship between the NPY gene rs16147 polymorphism and the presence of CAD in an Iranian population. Methods: DNA samples of 922 subjects, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…One of the most important variant within the promoter region upstream of the NPY is rs16147 (G-399 A) [6] and this genetic variant a substitution G to A (G as major allele and A as minor allele). This genetic variant has been related with serum levels of NPY [7], and it is related with more than half of the variation in the expression of this peptide [8] and this genetic variants of NPY gene could produce metabolic disorders associated with obesity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important variant within the promoter region upstream of the NPY is rs16147 (G-399 A) [6] and this genetic variant a substitution G to A (G as major allele and A as minor allele). This genetic variant has been related with serum levels of NPY [7], and it is related with more than half of the variation in the expression of this peptide [8] and this genetic variants of NPY gene could produce metabolic disorders associated with obesity [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the above-mentioned SNP has been shown to be related with serum levels of NPY [5] and to be responsible for more than half of the variation in the expression of NPY [6]. Few previous studies have shown an association between SNPs of NPY and early onset of atherosclerosis, stroke, and hypertension [7,8]. Moreover, adipose tissue is recognized as an endocrine organ producing several proteins, called adipokines, produced by adipose tissue (leptin, adiponectin, resistin, etc.).…”
Section: Introductionmentioning
confidence: 99%